Unveiling phytochemicals in P. guajava leaves: thin layer chromatography (TLC) investigation using methanol, chloroform and hexane / Wan Zahirul Syahmi Wan Bakree, Hannis Fadzillah Mohsin and Ibtisam Abdul Wahab - Wan Bakree, Wan Zahirul Syahmi; Mohsin, Hannis Fadzillah; Abdul Wahab, Ibtisam (Faculty of Health Sciences, Universiti Teknologi MARA, 2023)
Guava (Psidium guajava L.), a member of the Myrtaceae family, is a widespread tropical tree, grown in a wide variety of tropical and subtropical regions for its medicinal and nutritional properties. The fruit, bark, root, and leaves of the guava plant have all been used to treat various diseases and ailments. Guava leaves are the most often and extensively utilised part of the guava plant for traditional purposes, worldwide. Due to their diverse phytochemical composition, guava leaf extracts have been studied for their biological activities, including anticancer, antidiabetic, antioxidant, antidiarrheal, and antibacterial properties. In this study, P. guajava leaves were extracted by using organic solvents of different polarities. The groups of compounds in the extract were identified via thin-layer chromatography (TLC) and preliminary qualitative analysis. The leaves powder was macerated with methanol, chloroform, and hexane, in parallel. The TLC analysis was carried out by mixing hexane: ethyl acetate (7:3) and hexane: ethyl acetate (3:7) to identify polar and non-polar compounds in the guava leaves extracts. The preliminary qualitative analysis is performed to detect the presence of alkaloid and phenolics by using the Dragendorff's reagent and 5% ferric chloride solution. Results from the phytochemical screening shows the presence of flavonoids, terpene, alkaloids, carbohydrates, and phenolics. In summary, this project could provide valuable insights and supplementary details for the plant's monograph.